Spazi e politica nella modernità tecnologica - Bruna, Consarelli (Firenze University Press, 2006)
This notebook is the fourth in the series designed to illustrate the results of an interdisciplinary study group, fostered by Lea Campos Boralevi, Vittore Collina and Bruna Consarelli, lecturers in the history of political theory, entitled Figure dello spazio, politica e società, and aimed at exploring the major political and social issues of the modern and contemporary age from the aspect of spaces and their production. The contributions presented in this book address issues connected with the role and impact of technology.